The role of talent management in distinguishing business organizations - Mohamed, Kecna; Fatna, Gueiri (Journal of Excellence for Economics and Management Research, 2017)
This study aims to find out the role that talent management plays -as one of the new topics in the field of human resources’ management- in organizations, in order to achieve the brilliance it aspires to achieve. In addition to identifying the most important models of talent management and how to deal with them because of their role in achieving competitive aspect and its direct impact on performance levels. The researchers conducted this research in a method of library’s extrapolation which involves reviewing the exposed literature and discussing the concept of talent managements.